2018
DOI: 10.1021/acs.orglett.8b01228
|View full text |Cite
|
Sign up to set email alerts
|

Cu(I)-Catalyzed Aminative Aza-Annulation of Enynyl Azide using N-Fluorobenzenesulfonimide: Synthesis of 5-Aminonicotinates

Abstract: An unprecedented copper-catalyzed aminative aza-annulation of enynyl azide using commercially available N-fluorobenzenesulfonimide (NFSI) as an amination reagent is described. The reaction proceeds via regioselective inter-/intramolecular diamination, incorporating one nitrogen from the NFSI and the other from the azide, to provide amino-substituted nicotinate derivatives in a single step with moderate to high yield. This method represents an efficient way to access diverse aminonicotinates through direct C-N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 64 publications
(17 reference statements)
0
21
0
Order By: Relevance
“…Then, the Reddy group developed a copper-catalyzed aminative aza-annulation of enynyl azides with N -fluorobenzenesulfonimide (NFSI) to provide amino-substituted nicotinate derivatives 8 in good to excellent yield ( Scheme 4 ) [ 50 ]. The investigation showed that the electronic effect of the residue R on the substrates influences the results significantly.…”
Section: Reviewmentioning
confidence: 99%
“…Then, the Reddy group developed a copper-catalyzed aminative aza-annulation of enynyl azides with N -fluorobenzenesulfonimide (NFSI) to provide amino-substituted nicotinate derivatives 8 in good to excellent yield ( Scheme 4 ) [ 50 ]. The investigation showed that the electronic effect of the residue R on the substrates influences the results significantly.…”
Section: Reviewmentioning
confidence: 99%
“…The proposed mechanism was very similar to previous system reported by these authors. 36,43 Based on Li´s findings, Ranjan and co-workers developed a method for the synthesis of amino nicotinates 45 by aminative aza-annulation of enynyl azides using NFSI (Scheme 29a). The reaction took place by regioselective inter-/intramolecular diamination: one nitrogen atom from the NFSI and the other from the azide.…”
Section: Radical Additions To Alkynesmentioning
confidence: 99%
“…NFSI can act as a source of both fluoronium cation for fluorination and nucleophilic nitrogen or nitrogen radical for amination. 14 So far, few groups have explored the transition-metal-catalyzed amination of arenes with NFSI (Scheme 1a). 10 Recently, Pan and co-workers described a copper-catalyzed imidation of heterocycles such as thiophene, furan, and pyrrole with NFSI (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%